Severe Combined Immunodeficiency Disorder due to a Novel Mutation in Recombination Activation Gene 2: About 2 Cases - Ibtihal Benhsaien; Fatima Ailal; Khadija Elazhary; Jalila El bakkouri; Abdallah Badou; Ahmed Aziz Bousfiha (Case Reports in Immunology)
Severe combined immunodeficiency (SCID) comprises a heterogeneous group of inherited immunologic disorders with profound defects in cellular and humoral immunity. SCID is the most severe PID and constitutes a pediatric emergency. Affected children are highly susceptible to bacterial, viral, fungal, and opportunistic infections with life-threatening in the absence of hematopoietic stem cell transplantation. We report here two cases of SCID. The first case is a girl diagnosed with SCID at birth based on her family history and lymphocyte subpopulation typing. The second case is a 4-month-old boy with a history of recurrent opportunistic infections, BCGitis, and failure to thrive, and the immunology workup confirms a SCID phenotype. The genetic study in the two cases revealed a novel mutation in the RAG2 gene, c.826G > A (p.Gly276Ser), in a homozygous state. The novel mutation in the RAG2 gene identified in our study may help the early diagnosis of SCID.